PENGARUH ECONOMIC FREEDOM TERHADAP PERTUMBUHAN EKONOMI DAN FOREIGN DIRECT INVESTMENT (FDI) DI ASEAN - Iis Dayanti; Syamsul Amar B (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determined the effect of noneconomic variable on the economy, this study involves the role of government and institutions as factors that can affect the economy. Independent variable in this study is economic freedom, government size, rule of law, and investment freedom. Then, dependent variable in this study is PDB and FDI. This study used panel data in ASEAN for the 2008-2017 period. The model in this study is simultaneous panel with Two-Stage Least Sqares (2SLS) method. The result is economic freedom and government size have significant effect on PDB under fixed effect model and government size and investment freedom have significant effect on FDI under fixed effect model. But, rule of law in this study does not have significant effect on FDI.